Development of Chatbot Integration in Personal Finance Management Applications Using Generative Pre-Trained Transformer (GPT) 4o - Sawali Wahyu; Tomflynn Beltsazar (Bulletin of Computer Science Research, 2025)
Financial management is considered a crucial aspect considering the importance of financial matters in life. However, based on the survey of 13 Employees and 2 Parallel Students of Esa Unggul University revealed that most don't regularly record their finances. The reasons cited includes time constraints and lack of understanding. Additionally, none of the respondents used a financial recording application due to perceived complexity and inefficiency. To overcome this, a chatbot-based personal finance management application was built. The chatbot feature in this application is supported by the GPT-4o model and implemented by performing rapid engineering, which aims to simplify and streamline financial records. The app will be developed using the Mobile-D method, which includes five stages: explore, initialize, productize, stabilize, and system test & fix. The purpose of this study is to integrate chatbot features to simplify and accelerate the financial recording process. To evaluate its effectiveness, the app will undergo System Usability Scale (SUS) and User Acceptance Testing (UAT). The SUS resulted in a score of 77.16, categorized as "Good," while the UAT showed positive user feedback. These results show that the integration of chatbots with financial applications has successfully helped users manage their finances more easily and efficiently. This study proves the potential of chatbot technology integration in personal finance management, offering user-friendly solutions to overcome common obstacles in financial record keeping.